Application of technology for maximizing lean growth - Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1989)
The swine industry is at a crossroads that either mayor may not change the way we produce pork in the future. As we head into the 90's, we are entering a new era in terms of growth promotion and carcass modification,which will produce overnight what would have taken generations to select for. Of the compounds tested, porcine somatotropin (pST) has the most potential to alter the structure of the swine industry. Many fear the application of this technology because of potential increases in pork production displacing and leading to fewer producers. Because pork quality will be improved tremendously (50% reduction in fat and 5 to 25% increase in protein), this will offset the increase in production by increasing demand for lean pork (initial estimates of 4 to 5%). However, it still remains to be seen if adoption of this technology will be economically feasible. I believe that the adoption of pST technology will have a beneficial impact on pork production and, as a result, increase the profit potential by approximately 8.00 to 16.00 per head, whether you are finishing five or five thousand pigs per year. Although many questions still remain to be answered, in this paper I will attempt to put together as complete a picture as possible to determine the economic impact of pST on the swine industry.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Pig; Porcine somatotropin; Growth and development; Carcass composition; Economics